(untitled) (The Pretoria Student Law Review, 2021)
On 14 December 2000 South Africa signed the UN Protocol to Prevent, Suppress and Punish Trafficking in Persons, especially Women and Children (‘the Palermo Protocol’), and on 20 February 2004 ratified it. In so doing, South Africa committed itself to criminalising trafficking and developing legislation to combat it. On 3 October 2007 Essop Pahad, speaking at the Global Initiative to Counter Human Trafficking International Forum, said the National Prosecuting Authority had been tasked with coordinating this process and had formed an inter-sectoral task team to oversee the development of legislation. He further stated that provisions on trafficking had already been included in the Children’s Bill and that the revised Sexual Offences Act would have a chapter dealing specifically with trafficking for sexual purposes. On 16 December 2007 the Criminal Law (Sexual Offences and Related Matters) Amendment Act 32 of 2007 came into effect. It contains a chapter specifically dealing with trafficking as well as a section specifically addressing the issue of trafficking for sexual purposes. Although these provisions are only temporary, as they are not in full compliance with the Palermo Protocol, the South African government made an attempt to deal with the problem of trafficking, which up to that point had not been regulated by adequate legislation. In March 2009 Manto Tshabalala-Msimang, then Minister in the Presidency, stated that ‘the process of translating South Africa’s international commitments into national legislation is at an advance (sic) stage’. In 2008 government considered the idea of legalising prostitution for the duration of the 2010 FIFA World Cup. If prostitution were legalised, either for the duration of the World Cup or at any time thereafter, it would contradict the provisions of Part 6 of Act 32 of 2007 and nullify the work that has been done in an attempt to curb this crime of trafficking.